2022
DOI: 10.3389/fcell.2021.809620
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-Resistant Biomarkers in Bladder Cancer are Associated with Tumor-Immune Microenvironment

Abstract: To identify key biomarkers in gemcitabine (GEM)-resistant bladder cancer (BCa) and investigate their associations with tumor-infiltrating immune cells in a tumor immune microenvironment, we performed the present study on the basis of large-scale sequencing data. Expression profiles from the Gene Expression Omnibus GSE77883 dataset and The Cancer Genome Atlas BLCA dataset were analyzed. Both BCa development and GEM-resistance were identified to be immune-related through evaluating tumor-infiltrating immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…It has been reported that PCOLCE may be associated with the immune microenvironment of tumors, with implications for tumor prognosis and the potential to become a tumor marker, a finding that is consistent with ours. [ 1 , 3 ] Although our conclusions are consistent, the mechanism of action involved is still unclear. However, from our findings, the following points may be appropriate explanations: first, PCOLCE expression was positively correlated with the level of immune infiltration, and the data model Immune-based prognostic signature for OV (IPSOV) provided by previous studies validated in multiple independent datasets showed that high immune infiltration was associated with low survival probability was associated with statistically significant differences.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that PCOLCE may be associated with the immune microenvironment of tumors, with implications for tumor prognosis and the potential to become a tumor marker, a finding that is consistent with ours. [ 1 , 3 ] Although our conclusions are consistent, the mechanism of action involved is still unclear. However, from our findings, the following points may be appropriate explanations: first, PCOLCE expression was positively correlated with the level of immune infiltration, and the data model Immune-based prognostic signature for OV (IPSOV) provided by previous studies validated in multiple independent datasets showed that high immune infiltration was associated with low survival probability was associated with statistically significant differences.…”
Section: Discussionsupporting
confidence: 54%
“…[ 2 ] and bladder cancer. [ 3 ] To date, there is no large data showing a clear association between PCOLCE and pan-cancer, therefore, we first used databases such as the cancer genome atlas (TCGA) and gene expression omnibus (GEO) for pan-cancer analysis of PCOLCE. We explored this in a group of factors, such as gene expression, survival status, DNA methylation, genetic alteration, and immune infiltration, to explore the potential molecular mechanisms of PCOLCE in pathogenesis and clinical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that metastasis and chemotherapy resistance are closely related [ 12 , 28 ]. Although many studies compare the molecular mechanisms at two time-points before and after the acquisition of anticancer drug resistance, it will be more important to clarify the sequential molecular mechanism of chemoresistance and to identify biomarkers for better treatment of BC [ 9 , 16 , 17 ]. Therefore, we established sequential GRC cell lines to understand acquiring chemotherapy resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is an activation of the epithelial-mesenchymal transition (EMT) process, which may be interpreted as a strategy to avoid chemotherapy [13][14][15]. The studies of the chemical resistance mechanisms that have been mainly identified so far have focused on the mechanism that reflects the phenotype of the final resistance acquisition through comparison of the difference between the existing cancer cell lines and the resistance-acquired cell lines [16,17]. Therefore, in order to better understand anticancer drug resistance to the characteristic of cancer with cell heterogeneity, it is necessary to understand the stepwise changes in the mechanism of chemical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The role caveolin-1 plays in the immune response has been well documented through the demonstration of T cell activation [ 17 ] and the organization of the immune receptors in their plasma membrane [ 20 ]. This protein also regulates immune cell infiltration [ 21 ] and promotes dendritic cell maturation [ 19 ]. Besides its effects on the immune components of the tumor stroma, the molecular interplay between Cav1 and cell metabolism has been established [ 24 ], with its high expression suppressing c-Myc-induced metabolic reprogramming with an impact on breast stem cancer cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%